Crowdfunding in the banking industry : adjusting to a digital era - Setälä, Kalle (2017)
In the aftermath of the global financial crisis, the funding ability of banks has declined resulting in a financial void for riskier enterprises, such as startups and early-stage companies. New financial service providers have emerged in response to the capital deficiency. A particularly prominent incarnation of alternative finance is crowdfunding, where the funding is gathered directly from the market, from several individuals, who invest relatively small sums to compound the target amount. Financial institutions are contemplating the use of crowdfunding, not only for its business implications but also as a preparation for the potential threats it may impose on the traditional finance industry. This thesis sets out to explore the potential use of crowdfunding in the banking industry by examining the key motivations of banks to enter the novel industry. First, the thesis aspires to determine which of the financial instruments, debt, equity or donations should a bank construct its crowdfunding mechanism around and secondly, determine if a bank should enter the market through an arms-length collaboration, by building a platform internally or by setting up an independent subsidiary. Additionally, banks’ motivations and attitudes towards novel financial technologies and the development of the industry are scrutinized. The research was conducted as a qualitative field research, where the primary data was collected from seven interviews. The interviewees are banking professionals working for banks in Finland, Germany, Netherlands and Switzerland. Additionally, a ministerial adviser, whose expertise encompasses the regulative issues of crowdfunding, was interviewed. The secondary data for this research consists of existing crowdfunding research and articles. The empirical analysis indicates that crowdfunding does not currently represent the key focus for banks, but is rather seen as an adjustment to digitalization and as a means of elevating their image. Lending-based crowdfunding instruments closely resemble banks’ current offerings and could be more easily implemented than their equity counterparts. On the other hand, equitybased crowdfunding could broaden banks’ current customer base and extend investors’ investment opportunities. However, facilitation of equity crowdfunding is not amongst banks’ core competences and would likely require banks to obtain vast external capabilities. The analysis shows that setting up a subsidiary for crowdfunding could provide the lightest regulatory environment for Finnish banks, while collaborating with an existing crowdfunding platform could facilitate the easiest entrance to the crowdfunding market.